MENGEKSPLORASI DAMPAK KEPEMIMPINAN AGILE DAN LOGISTIK BERBASIS AGEN TERHADAP EFISIENSI BIAYA PENGIRIMAN LAST-MILE: WAWASAN DARI J&T EXPRESS - Syafrianita, Syafrianita; Purnomo, Agus; Fachmi Rachmat Chaidar, Diar (LAND JOURNAL, 2025)
The logistics industry has experienced substantial transformation due to the rapid expansion of e-commerce and advancements in digital technology, necessitating enhanced efficiency in last-mile delivery (LMD) processes. In the context of increasingly intense global competition and intricate infrastructure challenges, J&T Express confronts the imperative of sustaining its competitive edge. To address this challenge, two approaches currently perceived as promising are Agile Leadership and Agent-Based Logistics, both of which can augment operational flexibility and distribution efficiency. However, the empirical exploration of the relationship between these two concepts within the framework of LMD remains limited. This study seeks to investigate the impact of Agile Leadership on LMD efficiency at J&T Express and to assess the extent to which Agent-Based Logistics contributes to improved distribution effectiveness. Employing a quantitative methodology, this research gathers data through surveys administered to managers and operational personnel at J&T Express, with data analysis conducted utilizing PLS-SEM techniques. The findings indicate that Agile Leadership significantly enhances LMD efficiency by fostering responsiveness and operational flexibility. Furthermore, Agent-Based Logistics has demonstrated efficacy in expediting deliveries and reducing distribution costs through the engagement of community participation. The synergy between these two approaches further fortifies J&T Express's competitiveness in navigating complex logistics challenges. This research provides both theoretical and practical implications, offering recommendations for logistics firms to adopt more adaptive and community-oriented strategies.